Principal’s Leadership Behaviours Influence on Teacher’s Job Satisfaction in Public Secondary Schools in Kenya (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of the study was to establish the relationship between principal’s leadership behaviours and teacher’s job satisfaction in public secondary schools in Bungoma North Sub County, Bungoma County, Kenya. More specifically, the study sought to establish the relationship among four principal leadership behaviours: directive, participative, supportive and achievement oriented in relation to teacher job satisfaction. Path Goal model effectiveness formed the theoretical framework. Principal’s leadership behaviours formed the independent variable for the study while teacher’s job satisfaction, the dependent variable. The study adopted descriptive survey research approach. The unit sample of the study was all the 51 secondary schools in Bungoma North Sub County. The target population comprised of all the 51 principals and 761 teachers in all the 51 secondary schools in Bungoma North Sub County. All the 51 Principals were purposively selected from the sampled schools as they were leaders in those schools. The actual sample size of 263 teachers was selected purposively, making the actual sample size of the study to be 314 respondents. Data was collected using two sets of self-administered questionnaires. Spearman rho was used to determine the degree of relationship between principal’s leadership behaviours and teacher’s job satisfaction. The study concluded that directive, supportive, participative and achievement oriented leadership behaviours had a significant influence on teacher’s job satisfaction. Teachers also preferred directive leadership behaviours as opposed to principal’s achievement oriented leadership behaviours. The study recommended policy reforms on the action plans that influence job satisfaction of teachers